Modification of Ghanaian traditional abatoɔ game to improve the quality of basic education - Boateng-Nimoh, Victor; Nantwi, William Kwabena (Research Journal in Advanced Humanities, 2020)
The study focused on using the traditional abatoɔ game as a pedagogical tool for teaching contents in different subject areas and to find out how it motivates learners to learn. The study adopted a qualitative research approach with action and descriptive research methods. It was underpinned by the ‘Game-Based Learning’ (GBL) theory. Artistic techniques such as drawing, painting, printing, and computer Graphics were employed to modify the Ghanaian traditional abatoɔ game to improve the quality of teaching and learning. The modified abatoɔ game was tested at M.A. Bediako Adventist Preparatory school, Amakom-Kumasi Ghana with a population of five hundred and eighty-seven (587) pupils. Out of this, purposive and convenience sampling techniques were used to select forty (40) basic one pupils, thirty-six (36) basic four pupils and thirty-nine (39) basic six pupils as sample for the study. Observation, tests, feedback cards, and opinionnaire were used to collect data for the study. The study revealed the possibility to modify traditional games into educational games with integration of different learning contents. The study concluded that, learning contents integrated into game reinforce learners’ understanding of learning concepts, motivate learners to learn and prepare in advance for studies. The modified abatoɔ game also have the potential of reducing the workload on teachers as different learning contents can be taught with a single game.